2017
DOI: 10.1002/bab.1505
|View full text |Cite
|
Sign up to set email alerts
|

3‐Hydroxypropionic acid production by recombinant Escherichia coli ZJU‐3HP01 using glycerol–glucose dual‐substrate fermentative strategy

Abstract: 3-Hydroxypropionic acid (3-HP) is an important platform synthesis block for sets of chemicals, but the relatively low production of 3-HP from biological sources presented major barriers for its industrial applications. In this study, a dual-substrate fermentative strategy by glycerol and glucose was proposed, and the aim was to evaluate the effect of different substrate addition strategies on the fermentation process. The results indicated that the optimal cosubstrate was glucose (20 g/L), and the enzymatic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…These results altogether indicate that the codon-optimized synthetic version of the 3-HP biosynthetic pathway was correctly expressed and functional in B. subtilis . There has been a report on positive effect of glucose addition to the 3-HP producing strain of E. coli grown on glycerol, increasing the 3-HP production by reducing the imbalance between the first and second step of the pathway ( Niu et al, 2016 ). To test whether this effect applies to our strain, we grew the h-syn- KpDhaB - PuuC in two conditions: (1) 1.2% glycerol as the sole carbon source and (2) 1.2% glycerol supplemented with 1.2% glucose.…”
Section: Resultsmentioning
confidence: 99%
“…These results altogether indicate that the codon-optimized synthetic version of the 3-HP biosynthetic pathway was correctly expressed and functional in B. subtilis . There has been a report on positive effect of glucose addition to the 3-HP producing strain of E. coli grown on glycerol, increasing the 3-HP production by reducing the imbalance between the first and second step of the pathway ( Niu et al, 2016 ). To test whether this effect applies to our strain, we grew the h-syn- KpDhaB - PuuC in two conditions: (1) 1.2% glycerol as the sole carbon source and (2) 1.2% glycerol supplemented with 1.2% glucose.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of glucose as a co-substrate was also found to improve the activity of the aldehyde dehydrogenase gene, and in turn, improve the 3HP production yields [36]. Niu et al [36] reported a 3.5-fold increase in the activity of the enzyme, which improved the 3HP production in flasks from 3.39 g/L (control-no addition of glucose) to 6.80 g/L. Optimization of the glucose concentration and feeding strategy improved the 3HP production to up to 17.2 g/L during fed-batch cultivation.…”
Section: Engineering Of E Coli Cells For the Conversion Of Glycerol mentioning
confidence: 95%
“…This strategy resulted in the engineering of an E. coli strain capable of producing up to 56.4 g/L 3HP in a fed-batch bioreactor, with the addition of glucose together with glycerol. The addition of glucose as a co-substrate was also found to improve the activity of the aldehyde dehydrogenase gene, and in turn, improve the 3HP production yields [36]. Niu et al [36] reported a 3.5-fold increase in the activity of the enzyme, which improved the 3HP production in flasks from 3.39 g/L (control-no addition of glucose) to 6.80 g/L.…”
Section: Engineering Of E Coli Cells For the Conversion Of Glycerol mentioning
confidence: 99%
“…This allowed reducing the accumulation of fermentation by-products (lactate and acetate). The benefits of adding glucose as a substrate were also verified by Niu et al [74]. AldH (KGSADH) activity was enhanced in the presence of glucose.…”
Section: Glycerol Routementioning
confidence: 67%
“…The glycerol route (CoA-independent) is probably the route most studied as 3-HP can be produced directly from glycerol in two steps (Figure 3) [36,52,[67][68][69][70]. Additionally, 3-HP can also be produced from glucose using glycerol as an intermediary [32,34,35,38,39,44,45,47,51,[71][72][73][74]. In this case, the carbon flux is often redirected to glycerol.…”
Section: Glycerol Routementioning
confidence: 99%